Adjuvant Icotinib in EGFR-mutated stage IB non-small cell lung cancer with high-risk factors: A retrospective case series - Mengzhi Cheng; Jianbin Zhang; Lili Jin; Caihua Yu; Zhonghai Xie; Dong Li; Qinhua Gu; Qibin Shen (PLoS ONE, 2025)
Primary results of the CORIN trial indicated that, compared with chemotherapy, icotinib significantly improved 3-year disease-free survival (DFS) in patients with Epidermal Growth Factor Receptor (EGFR)-mutated stage IB non-small cell lung cancer (NSCLC). However, evidence regarding the outcomes of adjuvant icotinib in patients with high-risk factors remains limited. This retrospective study evaluated the efficacy and safety of adjuvant icotinib in patients with EGFR-mutated high-risk stage IB NSCLC. We enrolled 37 patients with completely resected EGFR-mutated high-risk stage IB NSCLC. The median follow-up time was 31 months, and the 3-year DFS rate was 91.4%. Two patients experienced disease recurrence and were successfully switched to osimertinib upon identification of an EGFR (T790M) mutation. Although overall survival (OS) and central nervous system (CNS)-DFS data were not mature, no deaths or central nervous system metastases were observed by the end of follow-up. 29 (78.4%) patients experienced grade 1–2 adverse events (AEs), no grade 3 or higher AEs occurred. This study suggests a potential DFS benefit and well-tolerated profile of adjuvant icotinib in patients with EGFR-mutated high-risk stage IB NSCLC. However, longer-term follow-up is necessary to assess the long-term outcomes.